Tratamento térmico de filmes supercondutores do sistema BSCCO utilizando forno de micro-ondas doméstico - Silveira, João Borges da [UNESP] (2014)
In the present work, the preparation of superconducting films of the BSCCO system will be presented. From a commercially available powder with nominal composition Bi 1.8 Pb 0.4 Sr 2 CaCu 2 O x, a film was prepared and heat-treated at 800°C (B12CM800). Powder with a similar composition was produced by the Pechini method modified for this purpose and a film heat-treated at 810oC (B12SM810) was them prepared. Also produced by Pechini method, a powder with nominal composition Bi 1.8 Pb 0.4 Sr 2 Ca 2 Cu 3 O x was used to prepare other three films thermally treated at 780oC (B23SM780), 810oC (B23SM810) and 840oC (B23SM840). The films were grown on crystalline substrates of LaAlO 3 (100) and thermally treated in a domestic microwave oven (2.45 GHz, 1200 W) adapted suitably for this purpose. The structural properties were studied using X-ray diffraction techniques, XRD, and scanning electron microscopy, SEM. The XRD technique indicated the formation of the 2212 phase in the B12CM800, B12SM810, B23SM780 and B23SM810 films, as well as the appearance of the 2201 phase and the following secondary phases: Ca 2 PbO 4 and Bi 2 CaO 4 . The film B23SM840 also indicated the formation of 2223 besides the 2212 phase and aggregates. The SEM technique presented the formation of structures with plate shape, typical of this material, and a superficial formation of structures rich in Ca on all the films, except for the B23SM840 film, which showed only the formation of plates. The energy dispersive X-rays technique, EDX, was carried out to verify a likely nominal composition of the films corresponding to 2223 phase for the B23SM840 film and 2212 phase for the others. The electrical measurements were made using the four-probe method, enabling the identification of the critical transition temperatures, T c, T c-onset, T c- midpoint and T c-offset, also the determination of the critical current density, J c . All films shown a characteristic T c of the 2212 ...